Tilted Snowplow Ponderomotive Electron Acceleration With Spatio-Temporally Shaped Ultrafast Laser Pulses - Wilhelm, Alex M.; Durfee, Charles G. (Frontiers in Physics, 2019)
We propose a novel scheme for using the ponderomotive force of a tilted ultrafast laser pulse to accelerate electrons in free space. The tilt of the intensity envelope results from the angular dispersion of the pulse's spectrum and slows down the interaction of the pulse with free electrons. The slower effective pulse velocity allows time for the electrons to accelerate from rest while remaining on the wave. We present both non-relativistic and relativistic analytic single-particle models in the adiabatic ponderomotive approximation, describing the process for an ideal infinite tilted pulse as well as a finite width beam. The analysis predicts the threshold intensity as a function of the pulse front tilt angle and shows that in the ideal case the output energy of the electrons is four times that of the ponderomotive potential at the capture threshold. Full-field simulations using the 2D OSIRIS 4.0 particle-in-cell code confirm the basic scheme. This tilted pulse acceleration scheme shows promise as a lab-scale method of accelerating electrons to the MeV level with good energy and angular resolution, to be used for ultrafast electron diffraction or injection into a second stage accelerator.